The Value of Mean Platelet Volume in Predicting The Severity of Preeclampsia and of Hellp Syndrome - Pınar Kumru; Nurettin Aka; Gültekin Köse; Özgür Kartal; Sacide Atalay (Medical Network, 2007)
OBJECTIVE: Assessing the value of MPV in predicting the severity of preeclampsia, and HELLP syndrome. STUDY DESIGN:12 women with HELLP syndrome,57 severely preeclamptic,30 mildly preeclamptic, 170 healthy pregnant women were included in this study and their MPV are recorded. RESULTS: The calculated sensitivity was 53% for mild preeclampsia,77% for severe preeclampsia, and 83% for HELLP syndrome. CONCLUSION: The measurement of MPV is not enough for diagnosis but can be useful with other sensitive tests.